(untitled) (Semiárida, 2020)
The aim of this work was to evaluate productive characteristics in different seasons of the year, of natural Rio Grande do Sul pastures grazed by rearing beef heifers, using metaanalysis. Nine experiments carried out from 2000 to 2009 were used. Herbage mass (HM), stocking rate (SR), and average daily gain (ADG) were the variables used. The sample units relative to season of the year were compared by random tests with the Euclidian Distance as the measure of similarity using the MULTIV software. The highest HM values were found during the seasons with the highest average temperatures (autumm, summer and spring), although the spring did not differ from the winter. Stocking rate was higher in autumm, summer and spring and lower in winter. Summer did not differ from the other seasons. Average daily gain was highest in spring and the other seasons did not differ among themselves. It is possible to obtain animal weight gain in natural pastures all year long, however the best results were observed during the warmer seasons.